Rapid isolation of plasma membranes in high yield from cultured fibroblasts. - Thom, D (1977)
1. A method was developed which allows the rapid preparation of pure plasma membranes in high yield from cultured fibroblasts. 2. Cells are lysed in hypo-osmotic borate/EDTA and, after differential centrifugation, the membranes collected by centrifugation on a sucrose barrier. 3. Electron microscopy of the isolated material shows large membrane vesicles essentially free from contaminating organelles. 4. There is no detectable activity of the endoplasmic-reticulum enzyme marker, NADH2--lipoamide oxidoreductase (EC 1.6.4.3), and that of succinate dehydrogenase (EC 1.3.99.1), a marker for mitochondria, is substantially decreased. Chemical compositions are in good agreement with previous observations. 5. This study confirms the usefulness of applied isotopic markers for isolating plasma membranes.